Wyjść poza krąg. O przywracaniu pedagogiki Marii Rogowskiej-Falskiej i Wiery Schmidt - Wojciech Siegień (Problemy Wczesnej Edukacji)
In the article, based on theoretical assumptions about framing mechanisms taken from the work of Georg Lakoff and the Polish tradition of post-dependence research, the author conducts a comparative analysis of cases of reframing the hegemonic and strongly patriarchal narratives regarding the pedagogical legacy of Janusz Korczak and Ivan Jermakov. As a result of systemic changes after 1989, narratives so far suppressed have come to the fore. It applies to minority voices, especially female voices. The comparative analysis took into account the voices of female educators from Poland and the Soviet Union – Maria Rogowska-Falska and Vera Schmidt. The main questions concern how hegemonic pedagogical discourses may erode and whether the processes of redefining pedagogical thought in Poland are analogous to trends in other countries of Central and Eastern Europe? The study points to far-reaching analogies of the processes of reframing in Poland and Russia. This has its consequences for our understanding of the achievements of Janusz Korczak in Poland and the roots of psychoanalysis in the Soviet Union.